Effects of single and combined water, sanitation and hygiene (WASH) interventions on nutritional status of children: a systematic review and meta-analysis - Zemichael Gizaw; Alemayehu Worku (Italian Journal of Pediatrics, 2019)
Abstract Background Under nutrition is linked with poor water, sanitation and hygiene (WASH) condition. However, there is conflicting evidence on the effect of WASH on nutritional status of children. This review was, therefore, conducted to estimate the pooled effect of WASH interventions on child under nutrition. Methods All published and unpublished cluster-randomized, non-randomized controlled trials, and before and after intervention studies conducted in developing countries were included. Relevant articles were searched from MEDLINE/PubMed, Cochrane Collaboration’s database, Web of Science, WHO Global Health Library, Google Scholar, Worldcat and ProQuest electronic databases. The methodological quality of the included studies was assessed using JBI critical appraisal checklist for randomized and non-randomized controlled trials. The risk of bias was assessed using the Cochrane Collaboration’s tool for assessing risk of bias in randomized trials. The treatment effect was expressed as standardized mean differences (SMD) with 95% confidence interval (CI). Results This meta-analysis of 10 studies including 16,473 children (7776 in the intervention and 8687 in the control group) indicated that WASH interventions significantly associated with increased pooled mean height-for-age-z-score (SMD = 0.14, 95% CI = (0.09, 0.19); I2 = 39.3%]. The effect of WASH on HAZ was heterogeneous in age and types of interventions. WASH intervention had more effect on HAZ among under two children [SMD = 0.20, 95% CI = (0.11, 0.29); I2 = 37%]. Children who received combined WASH interventions grew better compared with children who received single interventions [SMD = 0.15, 95% CI = (0.09, 0.20); I2 = 43.8%]. Conclusion WASH interventions were significantly associated with increased mean height-for-age-z score in under 5 years old children. The effect of WASH on linear growth is markedly different with age and types of interventions, either single or combined. Implementing combined WASH interventions has a paramount benefit to improve nutritional status of children.